2000
DOI: 10.1046/j.1439-037x.2000.00404.x
|View full text |Cite
|
Sign up to set email alerts
|

Sugarcane Breeding Institute, Coimbatore, India Effect of Different Levels of Drought during the Formative Phase on Growth Parameters and its Relationship with Dry Matter Accumulation in Sugarcane

Abstract: A field experiment was conducted at Coimbatore (11° N, 77° E), India during the 1996 and 1997 crop seasons, using four commercial sugarcane varieties (Co 8021, Co 419, Co 8208 and Co 6304), to study the effect of three levels of drought (severe, moderate and control) during the formative phase (60–150 days after planting) on growth determinants and their relationship with dry matter accumulation. The reduction in dry matter content was 60.8, 52.4 and 25.9 % in severe drought and 46.3, 36.3 and 15.1 % in modera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
62
0
13

Year Published

2007
2007
2023
2023

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 104 publications
(81 citation statements)
references
References 4 publications
4
62
0
13
Order By: Relevance
“…2a) and decreased green leaf area (Table 4). The formative phase (i.e., tillering and grand growth) has been identified as the critical water demand period and the phase during which sugarcane is most sensitive to drought (Ramesh, 2000). Water deficit decreased mean stalk weight and the number of stalks, resulting in low cane yields (De Silva and Costa, 2004).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…2a) and decreased green leaf area (Table 4). The formative phase (i.e., tillering and grand growth) has been identified as the critical water demand period and the phase during which sugarcane is most sensitive to drought (Ramesh, 2000). Water deficit decreased mean stalk weight and the number of stalks, resulting in low cane yields (De Silva and Costa, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…Water deficit decreased mean stalk weight and the number of stalks, resulting in low cane yields (De Silva and Costa, 2004). Ramesh (2000) suggested that measurements of growth variables during the formative phase may help predict sugarcane total biomass at final harvest. However, destructive measurements of biomass for a large number of samples are cost and time consuming.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The tillering and grand growth stages, known as the sugarcane formative phase, have been identified as the critical water demand period (Ramesh, 2000), mainly because this is the phase when 70-80% of cane yield is produced (Singh and Rao, 1987). Water relations and photosynthetic responses to water deficit stress during this growth stage could therefore be useful in identifying drought tolerant genotypes.…”
Section: Introductionmentioning
confidence: 99%
“…On senescence, Ramesh (2000) reports reduction in the energy expenditure for the formation of leaves after 279 DAH in sugarcane, which can also lead to LAI reduction. The values observed in both ratoons were close to those reported by Machado et al (1985), who found LAI close to 4 (m² m -²), which is sufficient to intercept 95% of the incident solar radiation.…”
Section: Resultsmentioning
confidence: 99%